Dynamic Assessment of Word Learning to Diagnose Developmental Language Disorder in French-Speaking Monolingual and Bilingual Children - Mélodie Matrat; Hélène Delage; Margaret Kehoe (Languages, 2022)
Dynamic assessment (DA), which evaluates the learning process rather than static knowledge, has been found to be effective in diagnosing developmental language disorder (DLD) in English-speaking bilingual children. We present three studies that examine whether a French dynamic word learning task can distinguish caseload children with DLD from control children with typical development (TD). Forty-eight monolingual and 69 bilingual French-speaking children, aged four to nine, were required to learn three to six non-words and their semantic characteristics. DA consisted of three phases: (1) a teaching phase in which non-words were taught to the child; (2) an immediate test phase, with graduated prompts, in which children were required to identify and produce the target words and their semantic features; and (3) a delayed test phase. Global results indicated that there were no differences between monolingual and bilingual TD children on the DA whereas there were differences on the static assessment of vocabulary knowledge: bilinguals performed less well than monolinguals. In addition, DA differentiated control and caseload monolingual children. Further work is needed to develop a dynamic word learning task, administered in one session, which can even more accurately differentiate TD and DLD bilingual children.